Intestinal Bacterial Communities of Trypanosome-Infected and Uninfected Glossina palpalis palpalis from Three Human African Trypanomiasis Foci in Cameroon - Jacob, Franck; Melachio, Trésor T.; Njitchouang, Guy R.; Gimonneau, Geoffrey; Njiokou, Flobert; Abate, Luc; Christen, Richard; Reveillaud, Julie; Geiger, Anne (Frontiers in Microbiology, 2017)
Glossina sp, the tsetse fly that transmits trypanosomes causing the Human or the Animal African Trypanosomiasis (HAT or AAT) can harbor symbiotic bacteria that are known to play a crucial role in the fly’s vector competence. We hypothesized that other bacteria could be present, and that some of them could also influence the fly’s vector competence. In this context the objectives of our work were: a) to characterize the bacteria that compose the G. palpalis palpalis midgut bacteriome, b) to evidence possible bacterial community differences between trypanosome-infected and non-infected fly individuals from a given AAT and HAT focus or from different foci using barcoded Illumina sequencing of the hypervariable V3-V4 region of the 16S rRNA gene. Forty G. p. palpalis flies, either infected by Trypanosoma congolense or uninfected were sampled from three trypanosomiasis foci in Cameroon. A total of 143 OTUs were detected in the midgut samples. Most taxa were identified at the genus level, nearly 50% at the species level; they belonged to 83 genera principally within the phyla Actinobacteria, Bacteroidetes, Firmicutes and Proteobacteria. Prominent representatives included Wigglesworthia (the fly’s obligate symbiont), Serratia and Enterobacter hormaechei. Wolbachia was identified for the first time in G. p. palpalis. The average number of bacterial species per tsetse sample was not significantly different regarding the fly infection status, and the hierarchical analysis based on the differences in bacterial community structure did not provide a clear clustering between infected and non-infected flies. Finally, the most important result was the evidence of the overall very large diversity of intestinal bacteria which, except for Wigglesworthia, were unevenly distributed over the sampled flies regardless of their geographic origin and their trypanosome infection status.